Human dignity and ethical treatment: Remarks on family concepts and family life in the era of the Reformation - Kirn, Hans-Martin (Nederduitse Gereformeerde Teologiese Tydskrif, 2011)
Martin Luther and the Reformation movement placed the household family anew at the centre of Christian life and ethics. In the wider sphere this religious “upgrading” cannot be overestimated in view of its effect on the process of confessionalization and modernization in European history. The education of children held a prominent place within the responsibilities of the household family; it was regarded as a divine task. Through this the Reformation movement intensified and specified humanist endeavours, which Erasmus summarized with the words: Human beings, believe me, are not born, but formed. Steven Ozment once maintained, that the family of the 16th century was a nurturing institution, characterized by love, respect and mutual dependence among the members of the family.